PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN SISTEM REMUNERASI TERHADAP MOTIVASI KERJA YANG BERDAMPAK PADA PRESTASI KERJA PEGAWAI POLITEKNIK LP3I JAKARTA - Enok Hapsah (POLITEKNIK LP3I JAKARTA, 2021)
The aim of this research is to analyze the influence of transformational leadership and remuneration system on employees performance with work motivation as an intervening variable (research was done at Polytechnic LP3I Jakarta). The amounts of these respondents are 103 employees of Polytechnic LP3I Jakarta. Sampling technique uses Accidental Sampling, and analysis technique uses path analysis, The result of the research shows that transformational leadership has a significant effect on work motivation, remuneration system has a significant effect on work motivation, transformational leadership has significant effect on employees performance, remuneration system has no significant effect on employees performance, work motivation has significant effect on the job performance, transformational leadership and remuneration system has a significant effect on employees work motivation, transformation leadership and remuneration system has a significant effect on employees performance.Keywords : Transformational leadership, remuneration system, employees performance and work motivation.